(untitled) (Editora Impacto Científico, 2025)
This chapter examines the interface between intellectual property and the Sustainable Development Goals (SDGs), proposing “green patents” as legal instruments that enhance sustainable innovation in the Brazilian agricultural sector. It begins by noting the high use of pesticides in the country and the need for technological alternatives with low environmental impact. As a case study, I present and analyze two inventions filed with the INPI (BR 10 2020 002755-7 and BR 10 2020 017615-3), developed by teams from UFRPE and IPA, as well as the 2020 article that provides the experimental basis for these technologies. I demonstrate how these culture media — based on forage cactus, mandacaru, and xique-xique — reduce production costs of δ-endotoxins by Bacillus thuringiensis, promote the use of local biodiversity, and align with SDG 2, SDG 12, and SDG 15. I also discuss the legal implications: compliance with the Biodiversity Law (Law No. 13.123/2015 and SisGen registration), challenges in university–industry technology transfer, and limitations of the patent system in fostering sustainable innovation. I conclude with recommendations for public policies and institutional practices that align intellectual protection and sustainable development in Brazil’s semiarid region. Personal contribution: As a researcher and inventor, I directly participated in the experimental work, in developing the cultivation protocols using cactus biomass, in the technical drafting of patent applications, and in coordinating between the university and research institutions. This practical experience supports the legal reflections proposed here, which aim to connect science, innovation, and law within a sustainability agenda. DOI: https://doi.org/10.56238/edimpacto2025.090-008